Effects of Stocking Density on Production Traits of Channel Catfish×Blue Catfish Hybrids. (7th August 2015) - Bosworth, Brian; Ott, Brian; Torrans, Les
Abstract: Channel Catfish Ictalurus punctatus × Blue Catfish I. furcatus hybrid fingerlings (mean weight, 47 g) were stocked in 0.4‐ha ponds at densities of 7, 425, 12, 375, 17, 325, 22, 275, and 27, 225 fish/ha in three replicate earthen ponds for each density. Fish were fed a 28% protein diet to apparent satiation once daily. Ponds were equipped with electric paddlewheel aerators (12.5 hp/ha) that were turned on when dissolved oxygen (DO) levels reached <5.0 mg/L; additional aeration was provided by power‐takeoff tractor‐driven paddlewheels at DO < 2.5 mg/L. Feeding was terminated at the end of October and fish were harvested and weighed. Stocking density had no significant effect on feed conversion (overall average, 1.97), survival (≥93% in all treatments), or processing yield (carcass yield = 66.2%, shank fillet yield = 34.8%, nugget yield = 10.5%). Harvest weight was not significantly different between 7, 425 and 22, 275 fish/ha (average, 0.85 kg) but was less at 27, 225 fish/ha (0.72 kg). Net production increased significantly with increased density from 7, 425 to 22, 275 fish/ha but was not different between 22, 275 and 27, 225 fish/ha. Percentage of submarketable fish (<0.45 kg) was not significantly different from pond densities of 7, 425 through 22, 275 fish/ha (average, 2.3%), but was higher at 27, 225 fish/ha (8.8%). Aeration hours increased and minimum DO levels decreased significantly as stocking density increased. The smaller average weight at 27, 225 fish/ha may have been due to fish behavior associated with crowding, lack of equal access to feed, or degraded water quality. However, past research has demonstrated a "threshold" relationship between minimum DO levels and catfish feeding and growth. Data from this study indicate a similar DO threshold–growth relationship, suggesting the observed effect of density on growth may have been at least partially due to minimum DO levels being below that needed for optimal growth at 27, 225 fish/ha.